Investigation on the Effect of Ultrasonication on the Morphology of BiVO4 Sonicated During and After Preparation by Chemical Co- Precipitation Method - Deebasree, J.P.; Maheskumar, V.; Vidhya, B.; Balaji, G. (University of Jaffna, 2019)
Bismuth vanadate (BiVO4) was synthesized by chemical co-precipitation and ultrasonic assisted coprecipitation method. The crystal structure of the samples was studied using X-Ray diffraction (XRD). The monoclinic scheelite structure was confirmed from the presence of (1 2 1) and (0 4 0) planes. The morphology and optical properties of the samples were analysed using scanning electron microscope (SEM) and UV–Vis diffused reflectance spectroscopy (DRS) respectively. Photocatalytic activity of the prepared BiVO4 was tested for the photo-degradation of Methylene Blue under visible light irradiation. The properties of as prepared BiVO4 is compared with the samples prepared using ultrasonic assisted coprecipitation method during and after preparation, and an optimal ultrasonic power output which leads to better photocatalytic activity is identified. The sample sonicated with 160 W during preparation yielded better catalytic efficiency which showed 93% degradation of Methylene blue. The improved catalytic activity could be attributed to its crystallinity, unique morphology and higher surface area compared to other samples.
Keywords: BiVO4; chemical precipitation; photocatalysis